Entre proximité et promiscuité. Vivre l’enfermement dans les petits espaces insulaires : le cas des îles de Ventotene et Santo Stefano (1770-1810) - Anthony Santilli (Criminocorpus)
In this contribution the attention is focused on confinement experiences produced in some small Italian islands. During the period 1770-1810, the Pontine islands of Ventotene and Santo Stefano, which represent our case study, are interested by three parallel projects: the colonization of Ventotene, the decision of making it a relegation island and the construction of a new penitentiary in Santo Stefano. After a description of these projects, we concentrate our attention on detention spaces, detentions conditions and treatment of prisoners. Finally, by some specific examples we want to bring the attention to the impact of these experiences on the whole insular society, despite the intention of Bourbon authorities to keep them separate.